2020
DOI: 10.22438/jeb/41/6/mrn-1449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitinase production on the antagonistic activity of Trichoderma against plant-pathogenic fungi

Abstract: Aim: The present study aimed to investigate the antagonistic activity of Trichoderma strains with high chitinase production against some plant pathogenic fungi. Methodology: A total of twenty-four Trichoderma isolates were extracted from soil samples collected at different geographical locations in Egypt and Saudi Arabia. These isolates were screened for their chitinase production ability using colloidal chitin media. Six isolates with high chitinase ability were identified as T. harzianum by internal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…and Rhizoctonia sp. [41]. Trichoderma asperellum PQ34 inhibited the growth of the Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 98%
“…and Rhizoctonia sp. [41]. Trichoderma asperellum PQ34 inhibited the growth of the Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Harighi et al (2007) indicated that chitinase 42 from Trichoderma atroviride PTCC5220 inhibited the growth of Rhizoctonia solani, a plant pathogenic fungus. Mazrou et al (2020) found the relationship between antagonistic activity of six Trichoderma harzianum strains against some plant pathogenic fungi such as Colletotrichum gossypii, Fusarium oxysporum, Fusarium fujikuroi, R. solani, Aspergillus calidoustus and Alternaria brassicicola and their chitinolytic enzyme production.…”
Section: Discussionmentioning
confidence: 99%